Closed-loop supply chain models with coopetition options. Issue 10 (19th May 2022) - Jalali, Hamed; Ansaripoor, Amir; Ramani, Vinay; De Giovanni, Pietro
Abstract : This paper proposes a Closed-loop Supply Chain game-theoretic model that mimics the DellReconnect Supply Chain. Within this framework, we characterise a game between an Original Equipment Manufacturer (OEM) and a social collector, who work together to recover electronics. The market comprises three segments: consumers purchasing only new goods, consumers purchasing only used goods, and indifferent consumers. The social collector decides whether the returns will be used to serve the used-market segment or the indifferent market segment first, thereby establishing the market structure and deciding whether to opt for competition or coopetition. We find that, whereas the social collector is indifferent when it comes to a choice between coopetition and competition, the OEM strictly prefers coopetition.